2023
DOI: 10.1001/jamacardio.2023.1469
|View full text |Cite
|
Sign up to set email alerts
|

Novel Association of the NOTCH Pathway Regulator MIB1 Gene With the Development of Bicuspid Aortic Valve

Idit Tessler,
Juliette Albuisson,
Rebeca Piñeiro-Sabarís
et al.

Abstract: ImportanceNonsyndromic bicuspid aortic valve (nsBAV) is the most common congenital heart valve malformation. BAV has a heritable component, yet only a few causative genes have been identified; understanding BAV genetics is a key point in developing personalized medicine.ObjectiveTo identify a new gene for nsBAV.Design, Setting, and ParticipantsThis was a comprehensive, multicenter, genetic association study based on candidate gene prioritization in a familial cohort followed by rare and common association stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 71 publications
(199 reference statements)
1
7
0
Order By: Relevance
“…Tangeretin could inhibit EndoMT in hiVECs ( Figure S14L ). These observations were consistent with the results of NOTCH1 deletion studies in vivo, 39 therefore, this protocol can be promising for its use in building heart valve disease models.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Tangeretin could inhibit EndoMT in hiVECs ( Figure S14L ). These observations were consistent with the results of NOTCH1 deletion studies in vivo, 39 therefore, this protocol can be promising for its use in building heart valve disease models.…”
Section: Resultssupporting
confidence: 88%
“…The scRNA-seq analysis demonstrated that NOTCH1 signaling pathway was important in the differentiation of hiPSCs into heart valve cells, and previous studies have reported that the NOTCH1 signaling pathway is critical for the development of heart valves. [37][38][39] In view of the crucial role of NOTCH1 in heart valve development, we sought to investigate whether inhibition of NOTCH1 might affect the differentiation of hiPSCs into heart valve cells. Tangeretin (an inhibitor of NOTCH1) significantly inhibited the differentiation of hiCLPMs and heart valve cells from hiPSCs (Figure S14C through S14G).…”
Section: Longitudinal Scrna-seq Analysis Reveals the Transcriptional ...mentioning
confidence: 99%
“…Her project eventually grew into a multinational collaboration involving 2 dozen investigators that identified a novel genetic cause for bicuspid aortic valve. 1 "We decided we wanted to go deeper and try to understand the wide spectrum of clinical expression of bicuspid aortic valve, " she said. "We realized that genetics may be the real story behind this inherited heart condition.…”
mentioning
confidence: 99%
“…Her project eventually grew into a multinational collaboration involving 2 dozen investigators that identified a novel genetic cause for bicuspid aortic valve. 1…”
mentioning
confidence: 99%
“…The prevalence of LVNC is generally increased in BAV cohorts, and mutation of KCNJ2, another potassium channel subunit, causes a syndromic presentation of BAV with extracardiac features in addition to arrhythmias (57). BAV and TAD also co-segregate with LVNC in some families with mutations in NKX2-5, TBX20 or MIB1, another Notch pathway regulator that was convincingly linked to BAV in recent studies and is recurrently mutated in the EBAV cohort (52,58,59). Our findings provide further evidence for a genetic link between cardiomyopathies, BAV, conduction abnormalities, and TAD that may contribute to early onset complications of BAV disease.…”
Section: Discussionmentioning
confidence: 97%